2.4 – Solving Equations with the Variable on Each Side
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1)
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1)
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k + 4.5
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k + 4.5
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = 4.5
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 =
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 =
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k = -9.5
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k =
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k =
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k = k = 19
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k = k = 19 Ex. 2 2(b – 3) = 3(b – 1)
REMEMBER: REVERSE Order of Operations! Ex. 1 4(k+3)+2 = 4.5(k+1) 4(k)+4(3)+2 = 4.5(k)+4.5(1) 4k = 4.5k k + 14 = 4.5k k -4.5k -0.5k + 14 = k = k = 19 Ex. 2 2(b – 3) = 3(b – 1) 2(b)–2(3) = 3(b)–3(1) 2b – 6 = 3b – 3 -3b -3b -b – 6 = b = b = -3